Pengaruh Konsentrasi Ekstrak Kulit Bawang Merah Terhadap Aktivitas Antioksidan dan Antibakteri Detektor Kesegaran Berbasis Selulosa -Antosianin - Adu, Risna Erni Yati (Fakultas Pertanian, Universitas Timor, 2024)
Chicken meat spoilage during storage can be monitored and prevented using smart packaging that contains active antioxidant and antibacterial compounds. This research aims to determine the effect of shallot skin extract concentration on the antioxidant and antibacterial activity of anthocyanin cellulose films for active packaging development. The method used to test antioxidant activity was the DPPH (1,1-diphenyl-picrylhydrazyl) method, while the antibacterial activity test used the liquid diffusion method. Antioxidant activity test results showed that the cellulose-anthocyanin film has an IC50 value of 1.36 Âµg/mL which was classified as very strong antioxidant activity. The antibacterial activity thest showed that overall the cellulose-anthocyanin film could inhibit the growth of bacteria, both Staphylococcus aureus and Escherichia coli bacteria. Shallot skin extract can be used as anthocyanins source which have antibacterial and antioxidant activity for smart packaging development.